Adolescent mothers' anthropometrics and grandmothers' schooling predict infant anthropometrics in Ethiopia, India, Peru, and Vietnam. Issue 1 (24th October 2017) - Schott, Whitney; Aurino, Elisabetta; Penny, Mary E.; Behrman, Jere R.
Abstract: We investigated intergenerational associations of adolescent mothers' and grandmothers' anthropometrics and schooling with adolescent mothers' offspring's anthropometrics in Ethiopia, India, Peru, and Vietnam. We examined birthweight ( n = 283), birthweight Z‐score (BWZ), conditional growth in weight‐for‐age Z‐score (cWAZ, residuals from a regression of WAZ at last survey round on BWZ, sex, and age), and height‐for‐age Z‐score (HAZ) of children born to older cohort adolescent girls in the Young Lives study. Our key independent variables were adolescent mothers' body size: HAZ and body‐mass‐index‐for‐age Z‐score (BMIZ) at age 8, conditional HAZ (cHAZ, residuals from a regression of HAZ at the end of a growth period on prior HAZ, age, and sex), conditional BMIZ growth (cBMIZ, calculated analogously), and grandmaternal BMIZ, HAZ, and schooling. We adjusted for child, maternal, and household characteristics. Adolescent mothers' cHAZ (ages 8–15) predicted birthweight ( β = 130 g, 95% confidence interval (CI) 31–228), BWZ ( β = 0.31, CI 0.09–0.53), and cWAZ ( β = 0.28, CI 0.04–0.51). Adolescent mothers' BMIZ at age 8 predicted birthweight ( β = 79 g, CI 16–43) and BWZ ( β = 0.22, CI 0.08–0.36). Adolescent mothers' cBMIZ (ages 12–15) predicted child cWAZ and HAZ. Grandmothers' schooling predicted grandchild birthweight ( β = 22 g, CI 1–44) and BWZ ( β = 0.05, CI 0.01–0.10).